The new politics of development in Latin America : the (dis)encounters of buen vivir and the political economy - Merino Acuña, Roger (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
The article approaches these issues by firstly discussing the foundations and scope of Buen vivir in relation to the different development theories grouped under the label of ‘alternative development’, particularly, human development. Then, it analyses the implementation of ‘Buen vivir’ policies in Bolivia and Ecuador and the tensions and problems derived from the translation of indigenous principles into a new development paradigm. Finally, it explains the emergence of ‘Buen vivir’ in the Peruvian Amazon and the possibilities and challenges it proposes to the dominant development theory and praxis.
Páginas 149-170
Keywords: Desarrollo humano--América Latina; Desarrollo económico--América Latina; https://purl.org/pe-repo/ocde/ford#5.00.00